ANALISIS KEBUTUHAN MEDIA KOMIK DIGITAL BERBASIS STEM UNTUK MENINGKATKAN LITERASI MEDIA SISWA SEKOLAH DASAR - Alwiyyah, Mila Muhimmatul; Purbasari, Imaniar; Amaliyah, Fitriyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the lack of student media literacy due to the lack of appropriate learning media. This research was conducted to produce media needs that can make things easier for students so that they can increase students' media literacy in elementary schools. This research was conducted on class V students at SDN 2 Prawoto. This study used mix methods with The explanatory sequential desaign. Data analysis uses descriptive data analysis using data obtained based on interviews, observations and distribution of questionnaires. The results of the research show that the learning media available in schools is still less attractive and the majority of students need learning media that can be applied, especially to science and science material in order to increase students' media literacy. The results of this research were obtained from the results of a needs analysis that 94.6% of the majority of students needed media. So in future research we will develop media that suits students' difficulties.